Shaping a Strategy for E-books: the JISC E-Books Working Group - Louise Edwards (Liber Quarterly: The Journal of European Research Libraries, 2002)
This paper outlines the strategy being developed for the growth of electronic books within the UK higher and further education sectors but the intention is that the broad strategic analysis will be of interest to all librarians.